2005
DOI: 10.1007/s10886-005-7617-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant Surface Properties in Chemical Ecology

Abstract: The surface of the primary aerial parts of terrestrial plants is covered by a cuticle, which has crucial autecological functions, but also serves as an important interface in trophic interactions. The chemical and physical properties of this layer contribute to these functions. The cuticle is composed of the cuticular layer and the cuticle proper, which is covered by epicuticular waxes. Whereas the cutin fraction is a polyester-type biopolymer composed of hydroxyl and hydroxyepoxy fatty acids, the cuticular wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
235
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(247 citation statements)
references
References 159 publications
2
235
1
9
Order By: Relevance
“…However, in nature the interface where tritrophic interactions take place is often the surface or more specifically, the cuticle of a plant (Müller and Riederer 2005). The cuticle proper contains two different wax portions: the intracuticular waxes embedded in the cutin matrix and a layer of epicuticular waxes encrusted above.…”
Section: Introductionmentioning
confidence: 99%
“…However, in nature the interface where tritrophic interactions take place is often the surface or more specifically, the cuticle of a plant (Müller and Riederer 2005). The cuticle proper contains two different wax portions: the intracuticular waxes embedded in the cutin matrix and a layer of epicuticular waxes encrusted above.…”
Section: Introductionmentioning
confidence: 99%
“…Direct defense mechanisms include morphological adaptations that impede herbivore colonization and movement on the plant, such as hairs, waxy leaf surfaces, or sticky secretions (van Dam and Hare 1998;Muller and Riederer 2005). Most plants also produce secondary metabolites that affect herbivore behavior and development.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was extensively studied [18], but few reports were found for the former. Yang et al found that five wild peanut species were more resistant to S. frugiperda larvae in feeding bioassays than a peanut cultivar.…”
Section: No-choice and Mortality Assays Against S Frugiperdamentioning
confidence: 99%